Pengaruh Aktivitas Fisik Pada Pasien Depresi - Arif Naufal (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
Depression is a critical illness that occurs throughout the world and can affect moods, ways of thinking, and behavior of patients. Depression can cause feelings of sadness and loss of desire to do activities that are popular. Depression also causes changes in variation in physical problems and a decrease in patients to work. Treatment for cases of depression is to use antidepressants. However, beyond this, there are no clinical trials that improve patients who get satisfactory recovery. Research shows that non-pharmacological therapy is quite promising as a therapy for depressed patients